Loneliness in sports active and non-active school-age children: Can sport protect children against loneliness? - Tubić, Tatjana; Modrić, Toni; Sekulić, Damir; Bianco, Antonino; Radjo, Izet; Drid, Patrik (Frontiers in Psychiatry, 2023)
This study aims to examine can sport protect children against loneliness and, if yes, whether this relationship depends on gender and/or sports-related variables. The sample includes 762 ten-year-old children (414 boys). The total score of The Children’s Loneliness Scale (Asher, Hymel, & Renshaw, 1984) is a dependent variable in the study, while sports participation (sports active – individual or team sports, or non-active) and level/duration of sports participation are independent variables. Obtained results indicate that the degree of loneliness differs depending on gender and whether the children are in sports activities or not. Unlike the level of sports participation, the duration of sports participation is relevant to the loneliness degree in both boys and girls. This research results could represent the right direction for educators and/or parents in their endeavor to preserve and develop school-age children's mental health.